Simple fluorescence-based detection of protein kinase A activity using a molecular beacon probe. Issue 6 (2nd November 2017) - Ma, Changbei; Lv, Xiaoyuan; Wang, Kemin; Jin, Shunxin; Liu, Haisheng; Wu, Kefeng; Zeng, Weimin
ABSTRACT: Protein kinase A was detected by quantifying the amount of ATP used after a protein kinase reaction. The ATP assay was performed using the T4 DNA ligase and a molecular beacon (MB). In the presence of ATP, DNA ligase catalyzed the ligation of short DNA. The ligation product then hybridized to MB, resulting in a fluorescence enhancement of the MB. This assay was capable of determining protein kinase A in the range of 12.5∼150 nM, with a detection limit of 1.25 nM. Furthermore, this assay could also be used to investigate the effect of genistein on protein kinase A. It was a universal, non-radioisotopic, and homogeneous method for assaying protein kinase A.